Optimal portfolio management. - Lim, Xue Jing. (2010)
This paper investigates the dual effect of stock selection and asset allocation method on optimizing equity portfolio performance, defined by risk-adjusted return. Portfolios are formed based on the four indicators, highest dividend yield, lowest price-earnings ratio, lowest price-to-book ratio and top loser stocks, and assets are then assigned weights using three different allocation approaches, equal-weight, value-weight and Markowitz optimization model that maximizes Sharpe ratio. We conclude that the 2 combinations: value-weighted lowest PE portfolio and value-weighted lowest PTB portfolio, generates best risk-adjusted returns, as measured by Sharpe ratio. However, these results are sensitive to changes in the sample used, investment horizon, short-sales constraints.